The Impact of Fuel Price on Energy Consumption on Indonesia’s Industries: A Firm-Level Analysis (Universitas Negeri Semarang, 2022)
This study aims to investigate the effect of energy price changes on energy consumption, especially oil and coal, for Indonesian manufacturing sectors. Unbalanced panel data analysis is utilized on firm-level data from 2003 to 2015 to examine the price elasticity of oil and coal demand. The estimation indicates that Indonesia’s manufacturing sectors are sensitive to energy price. On the aggregate analysis, one percent oil price increase is significant to reduce the demand of 0.194 percent, while coal consumption is not significantly affected by its price. Coal regression illustrates different outcomes than oil estimation which shows a positive relationship between coal price and coal demand even though it is insignificant. This phenomenon can be possibly interpreted through several explanations: a small number of firms using coal, concentration of coal demand in a few sub-sectors, and meager price of coal relative to oil. For further understanding, sectoral analysis has been examined on five priority sub-sectors—food and beverage; textile, apparel and footwear; chemicals and pharmacy; electronics and optical device; and automotive and transport equipment. The sectoral evaluations suggest that price elasticity for oil demand is considered as inelastic, ranging from 0.184 to 0.387 in absolute value. Oil price changes have the most impact on textile, apparel, and footwear sub-sectors, while food and beverage is the most unaffected by oil shocks.